Supplementary Vocational Education Contribution to Human Capital Development on Railway Transport - T. I. Syrodoeva; L. V. Lapidus (Вестник Научно-исследовательского института железнодорожного транспорта)
Human capital management of (just as management of any other sort accumulated resources) is of prime importance in the context of corporate management system. It is commonly known to comprise six functions, such as staff recruitment, leadership development, workforce planning, work execution control, professional training and employee retention. Each of them requires certain investment expenditures for generation and development. At the present time paradigm is being generated giving the palm to education in the context of human capital management and development. Special attention is paid to career broadening programs, insofar as supplementary professional education enhances the value of human capital. For closer affinity between professional education and business strategy training need estimation proceeds rather from the business feedback than from the employee one. The authors apply Becker’s approach (Howard Becker was one of the most talented modern economists) in the context of on-site professional training orientations (namely specialized and general ones) while treating them as peculiar study modes. As exemplified by JSC RZD and JSC VNIIZhT as its subsidiary there were discussed and analyzed approaches to specialized training issues covering a) enterprise system of vocational adaptation for employees and b) system of supplementary professional training and business education for managers and experts. Outcomes of the analysis paved the way for recommendation on the actualization of the JSC VNIIZhT human resource management strategy in the part of employee turnover. Refining of this strategy can be achieved through use of special-purpose ‘Plan for adaptation period upon entry into employment’ (draft plan is presented in the paper). The assessment problem of return on investments in human capital proves to be a rather topical one for business managers. That’s why the present paper contains calculation procedure to be used for economic appraisal of return on investments in the human resource training.